Sistem Cerdas Reservasi dan Pemantauan Parkir pada Lokasi Kampus Berbasis Konsep Internet of Things - Dody Ichwana Putra; Ratna Aisuwarya; Styviandra Ardopa; Indah Purnama (Jurnal Teknologi dan Sistem Komputer, 2018)
At present time, the people who use vehicles on the campus is increasing. It makes more difficult to find an empty slot parking area on the campus. This study aims to develop a system parking reservation and monitoring on-campus area using NFC and IoT concept. NFC was used to confirm booking code that generated by the system. In the parking area, ultrasonic sensors were installed to detect parking space availability. IoT concept has been applied to build this system. Apps on users smartphone can do the reservation process to the desired parking location via internet. Black box testing was done by building a prototype using the number of data locations parking slots in the Andalas University. The test results showed that this system has been able to detect the location of vacant parking slots and do reservations with time for sending data to the server is 0.7952 sec.